Probing the neural mechanisms of adult-onset isolated focal dystonia - QUINLIVAN, BRENDAN (Trinity College Dublin. School of Engineering. Discipline of Electronic & Elect. Engineering, 2018)
Adult onset isolated focal dystonia (AOIFD) is inherited in an autosomal dominant manner with a reduced penetrance of 12-15%; cervical dystonia (CD) is the most common phenotype in northern Europe. It is believed that the different phenotypes of AOIFD are cause by the same, currently unknown, genetic mutation(s). While the pathogenesis of AOIFD remains a mystery, recent animal and clinical studies have indicated its probable mechanisms. The temporal discrimination threshold (TDT) is the shortest interval at which two sequential stimuli appear to the observer to be asynchronous; a typically developing adult will have a TDT of 30 - 50 ms, although this varies with gender and age. It has been established that an abnormal TDT is a valid, sensitive and specific mediational endophenotype in several AOIFD phenotypes. The discovery of this mediational endophenotype has been instrumental in the formation of novel hypotheses regarding the pathogenesis of AOIFD. The hypothesis examined here states that both abnormal temporal discrimination and cervical dystonia are the result of a disorder of the midbrain network involved in covert orientation of attentional, caused by reduced gammaaminobutyric acid (GABA) inhibition in the superficial layers of the superior colliculus, resulting from undetermined genetic mutations. Such disinhibition is manifested in two ways: (1) subclinically, by abnormal temporal discrimination due to prolonged duration firing of the visual sensory neurons in the superficial laminae of the superior colliculus, (2) clinically by AOIFD due to disinhibited burst activity of the cephalomotor neurons of the intermediate and deep laminae of the superior colliculus. We tested this hypothesis by developing several experiments that involved the midbrain network for covert orientation of attention, specifically looking at various inputs and outputs from the superior colliculus in a principled and empirical manner. Three investigations were carried out to probe this hypothesis.
APPROVED
Keywords: Temporal Discrimination; Dystonia; Neural Engineering; Neuroscience; Dynamic Causal Modelling; fMRI; EEG; Movement Disorder; Superior Colliculus